Psychoeducational Guide for Climateric Women - Marianela Fonseca Fernández; Diana Maité Roselló Díaz; Laura Magda López Angulo; Alexis Lorenzo Ruíz (Revista Finlay)
The climacteric is a transition period that occurs between reproductive maturity, when hormonal changes and symptoms begin, until one year after menopause, where the loss of ovarian function occurs. In the development of the research, psychoeducational needs were identified in a group of 306 women from two areas of the Cienfuegos municipality. Based on this diagnosis, a psychoeducational guide for climacteric women was developed. The guide is designed with the intention of providing women in the climacteric period with the necessary guidance to face this stage of life and enhance their well-being. It is structured in sections related to the climacteric, its manifestations in the physical, psychological, sexual and social spheres, useful recommendations to manage the changes inherent to the stage and improve your well-being.